NOISE INTENSITY ANALYSIS OF TINNITUS COMPLAINTS IN COFFEE FACTORY WORKERS IN BANDAR DISTRICT, BENER MERIAH REGENCY IN 2020 - Lestari, Citra Yuli; Ariscasari, Putri; Santi, Tahara Dilla (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2023)
Background:Tinnitus is a health disorder that risks reducing worker productivity. Tinnitus is a common risk experienced by workers with high noise levels and long duration of noise exposure. Hearing loss in coffee factory workers can be caused by several factors including noise intensity, age, working hours per day, and length of service. The production section is a section that has a high risk of noise, this section carries out coffee grinding activities which require them to work optimally to produce quality products. Method: This research is descriptive analytic with a cross-sectional design. The population in this study were all workers from 3 coffee factories in Bener Meriah, totaling 47 people. The sampling technique uses the total population technique. Data collection was carried out using a questionnaire, then statistical tests were carried out using the chi-square test, and data were analyzed using SPSS. Results: All workers (100%) complained of tinnitus with varying degrees of severity, 89.4% of workers were young, 87.2% had no previous history of ear disease, 72.3% of working hours did not meet standards, 61.7% had been working for a long time. From the results of statistical tests, it can be concluded that there is a relationship between age (p value=0.002), working hours per day (p value=0.037), length of service (p value=0.001), and complaints of tinnitus in coffee milling factory workers. Only one variable, a history of ear disease (p value=0.078), was not associated with tinnitus complaints. Recommendation: It is recommended that every coffee grinding factory owner provide ear protective equipment (APT) for every worker in his factory to avoid complaints of tinnitus.